Clockwork angel [compact disc, unabridged] - Clare, Cassandra (Clare, Cassandra. Infernal devices, 2010)
When sixteen-year-old orphan Tessa Fell's older brother suddenly vanishes, her search for him leads her into Victorian-era London's dangerous supernatural underworld, and when she discovers that she herself is a Downworlder, she must learn to trust the demon-killing Shadowhunters if she ever wants to learn to control her powers and find her brother.